2009
DOI: 10.1128/mcb.01895-08
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Interaction between the Human DNA Repair Proteins DNA Ligase IV and XRCC4

Abstract: Nonhomologous end-joining represents the major pathway used by human cells to repair DNA double-strand breaks. It relies on the XRCC4/DNA ligase IV complex to reseal DNA strands. Here we report the highresolution crystal structure of human XRCC4 bound to the carboxy-terminal tandem BRCT repeat of DNA ligase IV. The structure differs from the homologous Saccharomyces cerevisiae complex and reveals an extensive DNA ligase IV binding interface formed by a helix-loop-helix structure within the inter-BRCT linker re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
150
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 42 publications
13
150
0
3
Order By: Relevance
“…The shorter X4 1-157 construct corresponded to a protein with a central coiled-coil that contained approximately 12 fewer helical turns (46 amino acids) than X4 1-203 construct. X4 1-157 did not contain the X4 residues involved in the L4 interaction (154-188) (21). Calorimetry measurements (Table 1) showed that X4 1-157 interacted with Cernunnos with a dissociation constant (Kd) of 4.1 AE 0.2 μM, which was similar to that obtained previously in studies using the longer construct X4 1-203 (Kd ¼ 3.9 AE 0.2 μM) (29).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The shorter X4 1-157 construct corresponded to a protein with a central coiled-coil that contained approximately 12 fewer helical turns (46 amino acids) than X4 1-203 construct. X4 1-157 did not contain the X4 residues involved in the L4 interaction (154-188) (21). Calorimetry measurements (Table 1) showed that X4 1-157 interacted with Cernunnos with a dissociation constant (Kd) of 4.1 AE 0.2 μM, which was similar to that obtained previously in studies using the longer construct X4 1-203 (Kd ¼ 3.9 AE 0.2 μM) (29).…”
Section: Resultssupporting
confidence: 71%
“…The association between Cernunnos and L4-X4 complex is mediated primarily through an interaction with X4 (14), although a weak interaction with L4 has also been reported (16). Cernunnos stimulates the ligase activity of the L4-X4 complex (20,21,(23)(24)(25) and seems particularly important for the ligation of mismatched or noncohesive DNA ends (25,26). Like X4, Cernunnos is a homodimer (27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined the binding pocket in the BRCT domains of Ligase4, XRCC1, BRCA1, and MDC1 because the structure of these BRCT domains has been solved (Zhang et al 1998;Sibanda et al 2001;Shiozaki et al 2004;Stucki et al 2005;Wu et al 2009;Campbell et al 2010;Cuneo et al 2011). However, the binding pockets in the BRCT domains of BRCA1 and MDC1 are much larger compared with those in the FHA domain.…”
Section: Computational Analysis Of the Par-binding Pockets In The Fhamentioning
confidence: 99%
“…The region between the two BRCT motifs of DNA ligase IV and part of the second BRCT motif are required for binding to XRCC4 [25,26]. DNA ligase IV and XRCC4 interact tightly and regulate one another's stability [27][28][29]. XLF, in contrast, is a weaker binding component of the ligation complex [30].…”
Section: The Process Of Nhejmentioning
confidence: 99%